Mucosal healing as a target of therapy for colonic inflammatory bowel disease and methods to score disease activity. - Walsh, A; Palmer, R; Travis, S (Elsevier, 2014)
Mucosal healing is an important therapeutic end point in clinical trials and clinical practice. There is no validated definition of mucosal healing in patients with inflammatory bowel disease, although the benefits of achieving mucosal healing include decreased need for corticosteroids, sustained clinical remission, decreased colectomy, and bowel resection. The Ulcerative Colitis Endoscopic Index of Severity is the only validated endoscopic index in ulcerative colitis. The Crohn's Disease Endoscopic Index of Severity and the Simple Endoscopic Score for Crohn's Disease are validated for Crohn disease, and the Rutgeerts Postoperative Endoscopic Index is used to predict recurrence after an ileocolic resection.